Environmental investigation using geophysical data at East Sadat City, Egypt - Sultan Awad Sultan Araffa; Shokry A. Soliman; Ahmed El Khafif; Abdellatif Younis; T.F. Shazley (Egyptian Journal of Petroleum)
Three geophysical techniques such as resistivity, seismic refraction, and GPR have been applied to delineate the depth to the groundwater surface, subsurface stratigraphy and subsurface structures which control the configuration and distribution of the groundwater aquifer. Five vertical electrical sounding (VES) were measured by using Syscal-R2 instrument of electrode separation ranging from AB/2 = 1–500 m to reach depth of investigation about 150 m. The results of quantitative interpretation of the VES data indicate that the subsurface sequence composed of six geoelectric units; the first unit is characterized by resistivity values up to 2007 Ohm.m corresponding to sand & gravel and thickness up to 1.2 m. The second geoelectric unit is corresponding to sandy clay which exhibits resistivity up to 235 Ohm.m and depth up to 1.2 m. The third geoelectric unit is characterized by resistivity values up to 1483 Ohm.m corresponding to dry sand which of depth up to 2.6 m. The fourth geoelectrical unit consists of sand saturated with ground water and exhibits resistivity values ranging from 20.2 to 52.9 Ohm.m and depth ranging from 7 to 16.8 m. The fifth geoelectrical unit reveals resistivity values ranging from 7 to 32.6 Ohm.m and consists of sandy clay saturated with groundwater of depth up to 111 m overlaying the sixth unit which reached to depth up to 165 m and characterized by resistivity values ranging from 54 to 91 Ohm.m corresponding to sandstone saturated with ground water. Five shallow seismic refraction spreads of geophone spacing 4 m were measured to investigate the subsurface sequence, where the results of interpretation indicate that the subsurface section consists of three seismic layers; the first layer is unsaturated overburden with seismic velocity range from 280 to 770 m/s and thickness reach about 6 m. The second layer is sand saturated with ground water with velocity range from 760 to 1300 m/s and maximum thickness of about 7 m overlaying the third layer reached to depth up to 24 m and corresponding sandy clay saturated with groundwater with seismic velocity range from 1130 to 2260 m/s. Five GPR profiles are measured using MALA RAMAC GPR System with a Rough Terrain Antenna (RTA) system of central frequency of 100 MHz. The interpretation of GPR data indicate that the expected water table ranging from 8 m to 11 m in the study area. Interpretation of the obtained results and correlation with the available geological and different geophysical data revealed that, the depth to the groundwater table of the investigated area ranges between 7 and 16.8 m. Keywords: Geophysical tools, GPR, Resistivity and seismic refraction